Household responses to disability shocks: Spousal labor supply, caregiving, and disability insurance - Siha Lee (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
This paper examines married women's time allocation to market hours and spousal care in the event of their husbands' disability and its implications for evaluating the insurance value of the Social Security Disability Insurance (SSDI) program. First, I find that while spousal labor supply responses to husbands' disability are small, wives spend a sizable amount of time in spousal care after their husbands become disabled. Motivated by these facts, I develop a dynamic model of married households that incorporates husbands' disability status, wives' time allocation choices, health state dependent utility, and the institutional features of SSDI. Counterfactual experiments indicate that caregiving needs substantially attenuate spousal labor supply responses and increase the insurance value of SSDI relative to its costs. Furthermore, policy
Keywords: D13; D15; H53; H55; I38; J22; 330; disability; social security; spousal labor supply; caregiving